Edukasi Terapi Slow Deep Breathing Pada Lansia Penderita Hipertensi Di Posyandu Lansia - Akbar, Fazri; Susanto, Amin; Suandika, Made (Yayasan Inspirasi El Burhani, 2025)
Introduction: Hypertension is a noncommunicable disease with a high prevalence among the elderly and can increase the risk of morbidity and mortality. This condition is a major concern because it can seriously affect the quality of life of the elderly and increase the risk of cardiovascular complications. Nonpharmacological therapy with slow deep breathing can improve blood flow in hypertensive patients with impaired blood flow, thereby lowering blood pressure. Objective: This study aims to improve the knowledge and skills of older adults in performing SDB therapy to control blood pressure. Method: The method used in this activity was education through lectures, demonstrations, and SDB training with a one group pretest-posttest design. A total of 31 elderly people participated in this activity. Result: The results showed a decrease in average systolic blood pressure before and after the intervention from 150.74 mmHg to 147.45 mmHg and diastolic blood pressure from 89.23 mmHg to 84.81 mmHg. In addition, most participants showed an improvement in their ability to perform slow deep breathing correctly. Conclusion: Education and training in slow deep breathing have been shown to have a positive impact on lowering blood pressure and increasing the independence of older adults in managing hypertension.